Analyzing small and medium enterprise lending activities - case study of MSB bank - Nguyễn, Thanh Hiếu (2020)
The thesis has systematized the theoretical issues of SME lending activities of commercial bank Based on the above theoretical framework, The thesis has conducted to research reports in same area and common analyzing ratio in order to assess the SME lending performance of MSB Bank and identify main factors affecting the SME lending activities in MSB Bank. For the purpose of study, necessary SME lending information of MSB Bank in the period of 2015 – 2017 in financial, HR aspects has been gathered from business management reports, HR reports, KPI reports. There are 02 interviews with high level management of SME Banking. Based on the analyzing quantitative and qualitative factors and ratios as well as the interview result, the study showed SME lending activities of MSB Bank was ineffective in comparison with other banks. Moreover, the strong points and weaknesses of MSB Bank in lending SMEs was identified. Then based on theories and interviews, author made some suggestions to improve the business performance of MSB in lending SME